2019
DOI: 10.3390/toxins11010022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Systemic Bleeding in Bothrops Envenomation in a Tertiary Hospital in the Brazilian Amazon

Abstract: Bothrops snakebites usually present systemic bleeding, and the clinical–epidemiological and laboratorial factors associated with the development of this manifestation are not well established. In this study, we assessed the prevalence of Bothrops snakebites with systemic bleeding reported at the Fundação de Medicina Tropical Dr. Heitor Vieira Dourado, in Manaus, Amazonas State, Brazil, and the clinical–epidemiological and laboratorial factors associated with systemic bleeding. This is an observational, cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 51 publications
(78 reference statements)
3
42
0
3
Order By: Relevance
“…Other symptoms and complications observed less frequently, such as hemorrhage, renal failure and septic shock, are also typical of bothropic envenoming (Souza 2002;Pardal et al 2004;Oliveira et al 2018;Roriz et al 2018). Altered blood clotting time had been observed in 43.1% to 72.2% cases of Bothrops envenomings in the Brazilian Amazon (Souza 2002;Pardal et al 2004;Moreno et al 2005;Oliveira et al 2019). The frequency in our study (82.5%) was more similar to that reported for Colombia (84.6%; Otero et al 1996).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other symptoms and complications observed less frequently, such as hemorrhage, renal failure and septic shock, are also typical of bothropic envenoming (Souza 2002;Pardal et al 2004;Oliveira et al 2018;Roriz et al 2018). Altered blood clotting time had been observed in 43.1% to 72.2% cases of Bothrops envenomings in the Brazilian Amazon (Souza 2002;Pardal et al 2004;Moreno et al 2005;Oliveira et al 2019). The frequency in our study (82.5%) was more similar to that reported for Colombia (84.6%; Otero et al 1996).…”
Section: Discussionsupporting
confidence: 84%
“…The frequency of mild, moderate and severe bothropic envenoming in our study (50, 36.5 and 13.5%, respectively), differed somewhat from that reported for the capital city of Acre state,Rio Branco (31.2,48.6 and 20.2%) (Moreno et al 2005). Severity frequencies were also reported for other Amazonian urban centers, such as Porto Velho (23.9, 26.1 and 50%), also in the southwestern Amazon (Roriz et al 2018), Manaus (27.7, 54.2 and 18.1%), in the central Amazon (Oliveira et al 2019), and Belém (58.1, 36.5 and 5.4%), in the eastern Amazon (Pardal et al 2004). These figures depend on the criteria used to define severity grades and the local context of accessibility to healthcare (Feitosa et al, 2015b), but may also be related to regional variations in the venom of Bothrops atrox (Núñez et al 2009;Sousa et al 2013;Del-Rei et al 2019).…”
Section: Discussionmentioning
confidence: 72%
“…Local effects vary from local pain to edema, blistering, hemorrhage, and myonecrosis [ 6 , 7 , 8 , 9 ] Systemic manifestations including bleeding, circulatory shock, and acute kidney injury have been strongly associated with fatal cases [ 1 , 5 ]. Additionally, severe local complications may be observed including necrosis, secondary infection and compartment syndrome [ 2 , 10 , 11 ]. In our study, the main symptoms observed were edema (98.5%), pain (97.7%), local hemorrhage (14.3%), blisters (14.3%), and local necrosis (10.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome is the installation of a consumptive coagulopathy, which is characterized by the depletion of hemostatic components. This depletion leads to unclottable blood and disruption of capillary vessels, which may be followed by bleeding [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clinical similarities of Bothrops envenomations in Brazil, thrombocytopenia is an infrequent event in Bothrops envenomation that occurs in the Amazon (caused mainly by B. atrox) compared to those in the southern region (caused by B. jararaca) [18][19][20]. Nevertheless, it has been shown that unclottable blood and thrombocytopenia are factors that are independently associated with the risk of systemic bleeding in Bothrops envenomations in the Brazilian Amazon [16].…”
Section: Introductionmentioning
confidence: 99%